GAMBARAN PENGGUNAAN ANTIBIOTIK PADA PASIEN PEDIATRI INFEKSI SALURAN PERNAPASAN AKUT (ISPA) DI KLINIK SINT. CAROLUS BENGKULU - Setya Enti Rikomah; Devi Novia; Septiana Rahma (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2018)
Antibiotics and infections are the most common problems faced by developing countries, including in Indonesia. Indonesia's awareness of the use of antibiotics rationally declines. Acute respiratory infections ranks first in terms of infant and under five mortality in developing and developing countries. This research was conducted to see the description of the use of antibiotics in patients with ISPA in Clinic Sint Carolus Bengkulu from January to December 2014. Data analysis was done by descriptive analysis with a retrospective method. The sample calculation was done by using the Slovin formula obtained by 100 samples. Of the 100 samples of this study, 57% of men and 43% of women, the age classification of acute respiratory infection was 0% of neonatal patients, 25% of infants, 32% of infants, 20% of children under five, and 23% of children, most antibiotics commonly used with ISPA is cefadroxil 60% amoxicillin 36% and erythromycin 3%, combination of TMP (trimethoprim) and SMZ (sulfamethoxazole) 1%. The type of ISPA that attacks is ISPA non pneumonia in the form of cough and cold based on medical record data at the Sint Carolus Clinic and the patient obtains the drug with a dose in safe range.